Severity and functional disability of patients with occupational contact dermatitis: validation of the German version of the Occupational Contact Dermatitis Disease Severity Index - Ofenloch, Robert; Diepgen, Thomas L.; Weisshaar, Elke; Apfelbacher, Christian (Contact dermatitis, 2015)
Background: The Occupational Contact Dermatitis Disease Severity Index (ODDI) was designed in Australia to measure severity and functional disability in patients with occupational contact dermatitis (OCD) of the hands. The ODDI was translated into the German language with a linguistic validation process. The psychometric properties of the German version of the ODDI are still unclear. Objectives:To report the linguistic validation procedure and to perform a psychometric validation by investigating the validity and reliability of the German ODDI version in a sample of patients with OCD. Methods;Data were drawn from the baseline assessment (T0) and first follow-up (T1) of the German chronic hand eczema (CHE) registry (CARPE). Spearman correlations of the ODDI with reference measures were computed to assess validity. Cronbach's alpha was calculated as a measure of internal consistency, and the intraclass correlation coefficient (ICC) was calculated to assess retest reliability. The smallest real difference (SRD) and minimal clinically important difference (MCID) were calculated to assess sensitivity to change. Physician Global Assessment (PGA) was used as an anchor for the MCID. Results: Four hundred and twenty-two patients (54.5% female, mean age 45.1 years) were included for analysis. Cronbach's alpha was found to be 0.73. The ICC was 0.79. Correlations between the ODDI total and the Dermatology Life Quality Index (rho = 0.36), and between PGA (rho = 0.48) and patient-assessed disease severity (rho = 0.40), were of moderate strength. The MCID (1.29) was found to be smaller than the SRD (1.87). Conclusions: The German ODDI version is reliable and valid for the measurement of functional impairment and disease severity in patients suffering from OCD.
Published online: Nov 19, 2014
Gesehen am 09.06.2017